QLTI-25. CREATING A CHEMOTHERAPY COMPETENCY METRIC FOR NEURO-ONCOLOGY FELLOWSHIP TRAINEES. (14th November 2022) - Peters, Katherine B; Patel, Mallika; Mrugala, Maciej
Abstract: Neuro-oncology fellowship trainees have varied academic backgrounds before subspecialty certification with most completing neurology residency ( > 90%) and a minority coming from medical oncology and neurosurgery programs. Given the variability in background and training of fellows, concerns about competency, particularly in prescribing chemotherapy and understanding associated toxicities, need to be addressed. Providing a metric to track and assess competency can enhance trainees' skills and bolster confidence during a neuro-oncology fellowship. In an IRB-exempt quality improvement project, we developed a competency test that was primarily case-based and guided knowledge of treatment indications, dosing, and management of associated toxicities. All questions were created based on NCCN guidelines and linked to a quality metric from ASCO-QOPI. Question content included 1. Prescribing, 2. Prescription review 3. Planning management, 4. Communicating information, 5. Drug dose calculation skills, 6. Adverse drug reactions, 7. Drug monitoring, and 8. Data interpretation. At the start of the fellowship, trainees took a pre-assessment test with a validated Likert scale for self-efficacy/confidence. These tests were scored, and directed elements were delivered via didactics to fellows by practicing neuro-oncologist and clinical pharmacist. The same assessments were performed at 6 and 12 months. All tests were scored and compared to the level of self-efficacy/confidence. Four fellows were included in this project across two institutions. Higher level of proficiency correlated with a higher level of self-reported confidence at the pre-assessment time point. Assessment at six months revealed an improvement in test scores and associated confidence and this trend continued at fellowship completion. This metric is the first known tool to evaluate chemotherapy competency and confidence in neuro-oncology fellows. Performance and self-efficacy/confidence are positively linked. This chemotherapy competency metric can be introduced to all neuro-oncology fellowship programs and used for national certification.